DIFFERENCES OF HPV VACCINANCE DIFFERENCES IN DEVELOPED COUNTRIES AND DEVELOPING COUNTRIES: LITERATURE REVIEW - Linda Friscitia; Yanti Hermayanti; Lilis Mamuroh (Journal of Maternity Care and Reproductive Health, 2020)
In 2012, there were 270,000 women around the world died becouse of cervical cancer. 99.7% of cervical cancers are caused by Human Papilloma Virus (HPV). HPV vaccination programs have been accepted in 77 countries, but around 87% of deaths occured in less developed areas. This study aims to determine the type of HPV vaccine used by both developed and developing countries in managing cervical cancer. This research method is a literature study, with a search using Epidence Based Practice (EBP) from databases such as Pubmed, Proquest, and Google Scholar. There are 10 articles based on searching results using PICO techniques. The instrument is critical appraisal cheklis from JBI QARI. The results of developed countries using this type of vaccine to fight CIN2 / 3 include DNA vaccines, HPV-18.VGX-3100, and AS04-adjuvanted HPV-16/18. Whereas developing countries use an effective type of HPV vaccine to prevent the outbreak of the HPV virus, namely the 2D-AS04-HPV-16/18 vaccine, quadrivalen, HPV-16/18-AS04-adjuvanted. MenACWY-TT, 2D-AS04-HPV-16/18 vaccine can be cost-effective. The conclusion of developed countries has developed a vaccine against CIN2 / 3 HPV-related high-type (16/18). Meanwhile, the developing countries especially in Indonesia just use HPV vaccine to prevent low HPV (6/11). It is suggested for women who will get HPV vaccine to choose an effective vaccine, and health personnel to be able to provide and do counseling about the effective vaccine as a form of cervical cancer prevention.